A Framework for Sustainable Implementation of E-Medicine in Transitioning Countries - Stephen Robert Isabalija; Victor Mbarika; Geoffrey Mayoka Kituyi (International Journal of Telemedicine and Applications)
Organizations in developed countries such as the United States of America and Canada face difficulties and challenges in technology transfer from one organization to another; the complexity of problems easily compounds when such transfers are attempted from developed to developing countries due to differing socioeconomic and cultural environments. There is a gap in the formation of research and education programs to address technology transfer issues that go beyond just transferring the technologies to sustaining such transfers for longer periods. This study examined telemedicine transfer challenges in three Sub-Sahara African countries and developed a framework for sustainable implementation of e-medicine. Both quantitative and qualitative research methods were used. The study findings indicate that e-medicine sustainability in Sub-Saharan Africa is affected by institutional factors such as institutional environment and knowledge management practices; technical factors such as the technological environment and technology transfer project environment; social environmental factors such as social environment and donor involvement. These factors were used to model the proposed framework.